2007
DOI: 10.1002/clc.20035
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Research Trends on Patient Factors in Patients with Implantable Cardioverter Defibrillators

Abstract: SummaryBackground: The implantable cardioverter defibrillator (ICD) is the most effective treatment available for terminating potentially life-threatening ventricular tachycardia and ventricular fibrillation and reducing the risk of mortality. Despite its established health benefits, ICD therapy is accompanied by a unique array of patient and psychological factors meriting ample research attention. The purpose of this paper is to examine research trends and results regarding patient factors in cardiac and ICD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
1
0
0
1
Order By: Relevance
“…With the goal of an individualised therapeutic offer for patients and their families, the present study supports the strategy already published in other paediatric collectives. 1,2,6,14,17,19,20,[64][65][66][67][68][69][70] Comparison of self-assessment and external assessment in our study showed good external assessments in younger children, while in adolescents symptoms seemed to be reported more often in the self-assessment than the external assessment. Therefore, the parent's role for identifying affected patients is rather in the younger children, whereas adolescents should be addressed in a selfassessment protocol.…”
Section: Discussionsupporting
confidence: 45%
“…With the goal of an individualised therapeutic offer for patients and their families, the present study supports the strategy already published in other paediatric collectives. 1,2,6,14,17,19,20,[64][65][66][67][68][69][70] Comparison of self-assessment and external assessment in our study showed good external assessments in younger children, while in adolescents symptoms seemed to be reported more often in the self-assessment than the external assessment. Therefore, the parent's role for identifying affected patients is rather in the younger children, whereas adolescents should be addressed in a selfassessment protocol.…”
Section: Discussionsupporting
confidence: 45%
“…15.000 Defibrillatoren (implantierbare Kardioverterdefibrillatoren; ICD) eingesetzt. Die Lebensqualität, das Erleben und die psychische Bewältigung der ICD-Implantation rücken zunehmend in den Fokus wissenschaftlicher Untersuchungen [1,2,3]. Während ein Großteil der Patienten mit dem ICD gut zurechtkommt und deutlich an Lebensqualität gewinnt [4,5,6], reagiert fast ein Drittel der Betroffenen bis zu 1 Jahr nach Implantation mit psychischen Beschwerden [7].…”
Section: Psychische Störungen Nach Icd-mehrfachschocks Und Deren Psycunclassified